SOCIAL COMPETENCY'S EVALUATION OF ADOLESCENTS WHO PRACTICE DANCE (Fiep Bulletin - online, 2015)
One of the necessities of the adolescence is accepted and understood by the acquaintances. In this way, the physical activity contributes like an important tool for a positive social integration. And in this context, appears the dance like propeller of the benefits of a physical activity, allies to the art and the culture, important and distinguishing aspects, mainly in a conflict and doubts period. The objective was to evaluate the level of the social competence of the dancers who participated of 16º Dance's Festival of the Shopping Itaguaçu, in Florianópolis (SC). The research was characterized as description-exploratory, with transversal delineation. The participants of the research had been composed for 82 dancers, of both genders and with ages between 10 and 22 years old, participants of 16º Dance's Festival of the Shopping Itaguaçu, in Florianópolis (SC). It was used as inclusion criterion, to integrate a group that practices dance at least for 6 months. As instrument was used the version of the The Group Environment Questionnaire (CARRON; BRAWLEY; WIDMEYER, 2002) translated and validated for the Brazil's Portuguese for Costa (2005). It was used the Descriptive Statistics, through simple and relative frequency, beyond mean and standard deviation. About the social competence, analyzing the means of both genders in the four aspects, Individual Attractions to the Group - Social, Individual Attractions to the Group - Task, Group Integration - Social and Group Integration - Task, it was met high values of group's cohesion. This is the same for the aspects related to the task and the social. Concluding, it is believes that the dance's practice provided to these practitioners a highest social competence; what can be demonstrated for the group's cohesion through the maintenance of positive social interactions, the close involvement with the group's integrants, the ability to work well in group, the feeling of individual importance for the team, as well as the creation of lies between the team, like a social unit.
Keywords: Social competency. Group's cohesion. Dance.